1996
DOI: 10.1016/0378-1097(96)00024-9
|View full text |Cite
|
Sign up to set email alerts
|

An inducible expression system of histidine-tagged proteins in Streptomyces lividans for one-step purification by Ni2+ affinity chromatography

Abstract: An expression and purification cassette containing the aminoglycoside phosphotransferase gene (aph) as selective marker has been constructed in the Escherichia coli vector pULHis2. DNA fragments inserted in the cassette can be easily subcloned in pIJ699 to give vectors for overexpression of genes in Streptomyces and purification of proteins by a one-step procedure. The expression system uses the thiostrepton-inducible promoter tipA for expression and a six histidine coding nucleotide sequence that is fused in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…One of the most widely used promoters used to drive inducible overexpression of cloned genes in Streptomyces is the tipA promoter, ptipA (Takano et al , 1995 ; Yu & Hopwood, 1995 ; Enguita et al , 1996 ). In its normal context in S. lividans , this promoter controls the synthesis of an mRNA transcript that itself encodes two different proteins: the 31 kDa TipAL and the 17 kDa TipAS (Murakami et al , 1989 ; Holmes et al , 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely used promoters used to drive inducible overexpression of cloned genes in Streptomyces is the tipA promoter, ptipA (Takano et al , 1995 ; Yu & Hopwood, 1995 ; Enguita et al , 1996 ). In its normal context in S. lividans , this promoter controls the synthesis of an mRNA transcript that itself encodes two different proteins: the 31 kDa TipAL and the 17 kDa TipAS (Murakami et al , 1989 ; Holmes et al , 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports used well characterized promoters of the nitrilase gene [10], acetoamidase gene [16], and tipA [11,12,17]. In S. coelicolor , the expression vector containing act I/ act III promoter was induced during the transition from the growth to the stationary phase to successfully produce polyketido synthases [18].…”
Section: Reviewmentioning
confidence: 99%
“…, previous studies have suggested that the gene products of cmcI and cmcJ may control 7 α ‐methoxylation of cephalosporins through successive steps of hydroxylation and methylation (Enguita et al . ,b). However, it was found that the bioconversion rate of CPC to MCPC was inefficient when the enzymatic reaction was conducted with cell‐free extracts of S. clavuligerus ATCC 27064, implying the low expression level of cmcI or cmcJ or both in the cell (O'Sullivan and Abraham ).…”
Section: Introductionmentioning
confidence: 99%